Pergeseran Kebijakan Ketahanan Pangan Global: Dari Revolusi Hijau Menuju Revolusi Genomik - Fahmid, Imam Mujahidin; Fahmid, Mirah Midadan; Badrani, Adib Gemilang (Jurnal Sosial Ekonomi Pertanian, 2025)
This study aims to: (1) analyze the epistemological shift from the Green Revolution to the Genomic Revolution in the global food system; (2) examine the opportunities and threats posed by genomic technologies to food security, particularly in the context of ecological and social justice; (3) explore the responses and strategies of countries such as Brazil, India, Rwanda, and Indonesia in dealing with genomic transformation; and (4) propose a conceptual and ethical framework for positioning genomics as a tool for community empowerment rather than merely a corporate technology. Employing a political ecology approach, literature review, and comparative case analysis, the study finds that the Genomic Revolution signifies a transition from the statistical-population paradigm of the Green Revolution to a more precise, adaptive paradigm of systemic biology. While genomics offers opportunities for increasing productivity, climate resilience, and nutritional quality, it also raises serious concerns over biogenetic data privatization, the marginalization of smallholder farmers, and corporate control over genetic resources. The case studies reveal that Brazil successfully integrates genomics and agroecology within a communitarian legal framework; India asserts resistance to transgenic seeds through participatory breeding; Rwanda incorporates genomics into nutrition interventions using open data; whereas Indonesia still faces institutional fragmentation and weak protection of local knowledge. These findings suggest that the success of the Genomic Revolution in promoting just and sustainable food security depends heavily on ethical governance and policy frameworks that ensure community rights to data, seeds, and scientific decision-making. Keywords: Genomic Revolution; Food Security; Epistemology; Ecological Justice; Political Ecology.